Efforts to Improve Learning Activities and Learning Outcomes of Mathematics Integer Materials Through the Application of the PBL Learning Model in Grade VI Elementary School Students - Widiana, I Wayan; Fadli, Moh. (Journal of Islamic Elementary Education, 2023)
The learning activities of Grade VI students at SD Negeri 2 Tri Eka Buana in mathematics are lacking and tend to be very passive. This can be seen from the absence of students' responses when asked questions, many students seem not interested in working on the questions given and there are still many students who are indifferent. The purpose of carrying out this PTK is to find out whether the application of PBL is able to improve learning activities and student learning outcomes. This research is a PTK type which involves one class. This research was conducted in two cycles where each cycle has the same activity stages, namely Planning, Implementation, Observation and Reflection. The subjects of this study were class VI students in the odd semester of the 2022/2023 school year with a total of 21 students consisting of 7 boys and 14 girls. The classical completeness criterion in mathematics is 65%. Data collection techniques used: (1) Observation sheets of student activity when giving action through observation. (2) Data on students' mathematics learning outcomes were obtained from the learning outcomes test cycle 1 and cycle 2 after being given treatment. The results of this study show that: (1) There was an increase in students' learning activities in the mathematics learning process in cycle 1. Student activity increased by 62.5% in cycle 2 to 70% included in the active category. (2) Student learning outcomes have increased, where cycle 1 reaches 61.9% or 15 students can achieve learning mastery at moderate criteria and in cycle 2 it increases to 76.2% or 18 students achieve learning mastery with high criteria . So it can be concluded that the application of the PBL model is able to increase learning activities and learning outcomes of students in mathematics class VI SD.